Plant growth promotion by the interaction of a novel synthetic small molecule with GA‐DELLA function. (26th April 2022) - Sukiran, Nur Afiqah; Pollastri, Susanna; Steel, Patrick G.; Knight, Marc R.
Abstract: Synthesized small molecules are useful as tools to investigate hormonal signaling involved in plant growth and development. They are also important as agrochemicals to promote beneficial properties of crops in the field. We describe here the synthesis and mode of action of a novel growth‐promoting chemical, A1. A1 stimulates enhanced growth in both shoot and root tissues of plants, acting by increasing both dry and fresh weight. This suggests that A1 not only promotes uptake of water but also increases production of cellular material. A1 treatment of Arabidopsis leads to the degradation of DELLA growth‐inhibitory proteins suggesting that A1‐mediated growth promotion is dependent upon this mechanism. We performed genetic analysis to confirm this and further dissect the mechanism of A1 action upon growth in Arabidopsis . A quintuple della mutant was insensitive to A1, confirming that the mode of action was indeed via a DELLA‐dependent mechanism. The ga1‐5 gibberellin synthesis mutant was similarly insensitive, suggesting that to promote growth in Arabidopsis A1 requires the presence of endogenous gibberellins. This was further suggested by the observation that double mutants of GID1 gibberellin receptor genes were insensitive to A1. Taken together, our data suggest that A1 acts to enhance sensitivity to endogenous gibberellins thus leading to observed enhanced growth via DELLA degradation. A1 and related compounds will be useful to identify novel signaling components involved in plant growth and development, and as agrochemicals suitable for a wide range of crop species.